Interpreting Psychiatrist’s Book Cover Design as Personal Branding Through Barthes’ Semiotics - Elisabeth Pratiwi; Mochammad Charis Hidayahtullah (Judikatif: Jurnal Desain Komunikasi Kreatif, 2026)
Book cover design is a critical element of visual communication that shapes how readers perceive both the content and the identity of an author. Within the mental health profession, the visual language of a book cover extends beyond aesthetics it carries personal values and reflects the professional character of its creator. This study analyzes the visual signs on the cover of Buku Seorang Wanita yang Ingin Menjadi Pohon Semangka di Kehidupan Berikutnya, a book by psychiatrist dr. Andreas Kurniawan, Sp.KJ, and interprets their semiotic meaning through Roland Barthes' theoretical framework. A qualitative-descriptive semiotic approach was adopted, applying Barthes' three levels of meaning: denotation, connotation, and myth. Analysis focused on visual elements including color palette, illustration, typography, and compositional layout. The findings reveal that the combination of soft green tones, a female figure surrounded by natural symbols, and sans-serif typography collectively project a visual impression that is calm, reflective, and humanist. At the mythological level, the design constructs ideological narratives centered on emotional healing, inner strength, and the psychiatrist's identity as an empathetic, approachable figure. Taken together, the visual communication design of this book cover plays a strategic role in reinforcing the professional personal branding of a mental health practitioner.